Allogeneic hematopoietic cell transplantation after failed autologous transplant for lymphoma using total lymphoid irradiation and anti-thymocyte globulin conditioning - Rezvani, Andrew R. (Bone Marrow Transplant, 2015)
We describe 47 patients with lymphoma and failed prior autologous hematopoietic cell transplantation (HCT) who received TLI-ATG conditioning followed by allogeneic HCT. Thirty-two patients had non-Hodgkin lymphoma (NHL; diffuse large B cell lymphoma [n=19], T-cell NHL [n=6], mantle cell lymphoma [n= 4], or other B-cell subtypes [n=3]), and 15 had Hodgkin lymphoma. The median follow-up was 4.9 (range, 2.1–11.9) years. The cumulative incidence of grade II–IV acute GVHD at day +100 was 12%, and the cumulative incidence of extensive chronic GVHD at 1 year was 36%. The 3-year cumulative incidences of overall survival, progression-free survival (PFS), and non-relapse mortality (NRM) were 81%, 44%, and 7%, respectively. Fifteen patients died (relapse, n=10; NRM, n=5). Among the 25 patients with relapse after allogeneic HCT, 11 (44%) achieved durable (>1 year) complete remissions following donor lymphocyte infusion or chemoradiotherapy. The majority of surviving patients (75%; n=24) were able to discontinue all immunosuppression. For patients with relapsed lymphoma after autologous HCT, allogeneic HCT using TLI-ATG conditioning is a well-tolerated, predominantly outpatient therapy with low NRM (7% at 3 years), a low incidence of GVHD, durable disease control, and excellent overall survival (81% at 3 years).